Variations of cannabis-related adverse mental health and addiction outcomes across adolescence and adulthood: A scoping review - Kaur, Navdeep; Bastien, Gabriel; Gagnon, Lea; Graham, Johann; Mongeau-Pérusse, Violaine; Bakouni, Hamzah; Morissette, Florence; Theriault, Camille; Fischer, Benedikt; Jutras-Aswad, Didier (Frontiers in Psychiatry, 2022)
Introduction: Evidence supporting associations between cannabis use and many health outcomes is growing, however it remains unclear how such associations vary across the lifespan. We therefore aim to answer the following questions: 1) Are the risks of cannabis’s adverse effects on mental health and addiction-related outcomes different in adolescents than in adults? 2) What are the relationships between these cannabis’s adverse effects and (a) an individual’s age at first cannabis use, (b) age at assessment, and (c) duration of cannabis use? Methods: We searched Medline, Embase, CINAHL, and PsychINFO from inception to 18 October 2021. Two reviewers independently screened studies and descriptively synthesized results. Results: We included 140 studies. Cannabis effects on mental health and addiction-related outcomes were worse in adolescents, early cannabis initiators and cannabis users who consumed for longest periods. Evidence of worse long-term adverse effects in adolescents was substantial for psychosis, cannabis, and nicotine use disorders; mixed for depression, suicidality, other substance use and disorders; and limited for anxiety. Additionally, acute cannabis exposure had the opposite trend with adults more often reporting adverse effects than adolescents. Conclusions: The available evidence suggests that cannabis use should be delayed as late as possible in adulthood and shortened in duration across the lifespan to decrease the risk of negative outcomes, while emphasizing the need for adapted harm reduction approaches. This scoping review provides evidence on the role of age and duration of exposure as determinants of cannabis-related adverse effects, which may inform prevention and harm reduction strategies.